Please help if you know how to solve it
Thank you!
Please help if you know how to solve it Thank - 1

Answers

Answer 1
Answer: 79a hope this helps!!! :)
Answer 2
Answer:

Answer:

opsihsjijjakih

Step-by-step explanation:

jiompzjksuik


Related Questions

The cost of a book is twice that of a magazine.1 book and 4 magazines cost £ 24. How much does a book cost?
Two functions, y = |x - 3| and 3x + 3y = 27, are graphed on thesame set of axes. Which statement is true about the solution to thesystem of equations?(1) (3,0) is the solution to the system because it satisfies the equationy = |x - 3|.(2) (9,0) is the solution to the system because it satisfies the equation3x + 3y = 27.(3) (6,3) is the solution to the system because it satisfies both equations.(4) (3,0), (9,0), and (6,3) are the solutions to the system of equationsbecause they all satisfy at least one of the equations.
The product of 9 and a number is 12 less than three times that number.What is the number? Giving 20 Points....
Which of the following expressions is the conjugate of a complex number with −5 as the real part and 4i as the imaginary part? 5 + 4i / 5 − 4i / −5 − 4i/ −5 + 4i
What is the highest common factor for 3876 and 114?

the lenghtvof each side of a square is 2.5 meter. if each side is doubled in length, what is the effect on the perimeter of the square? a.it remain the same b.it is one half the original perimeter c. it is four time the original perimeter d. it is twice the original perimeter.

Answers

Answer:

Step-by-step explanation:

Alright, lets get started.

The side length of square is given as 2.5.

So, the perimeter if square will be : 4*2.5=10.0

Once the side is doubled, means new dimension of side of square will be : 2*2.5=5

So the new perimeter will be : 4*5=20

The original perimeter is 10.

The new perimeter is 20.

It means the perimeter is twice the original perimeter.   :   Answer D

Hope it will help :)

T=4.5


Simplifying3t + 4 = t + 13
Reorder the terms:4 + 3t = t + 13
Reorder the terms:4 + 3t = 13 + t
Solving4 + 3t = 13 + t
Solving for variable 't'.
Move all terms containing t to the left, all other terms to the right.
Add '-1t' to each side of the equation.4 + 3t + -1t = 13 + t + -1t
Combine like terms: 3t + -1t = 2t4 + 2t = 13 + t + -1t
Combine like terms: t + -1t = 04 + 2t = 13 + 04 + 2t = 13
Add '-4' to each side of the equation.4 + -4 + 2t = 13 + -4
Combine like terms: 4 + -4 = 00 + 2t = 13 + -42t = 13 + -4
Combine like terms: 13 + -4 = 92t = 9
Divide each side by '2'.t = 4.5
Simplifyingt = 4.5



I got help from a website called geteasysolution

In a school, the ratio of musicians to athletes is 3:1. which statement is true13 of the total students are musicians.



If there are 18 people, then 12 of them are athletes.



If there are 3 athletes, then there are 12 musicians.



The number of musicians is 3 times the number of athletes

Answers

I think the correct answer from the choices listed above is the last option. In a school, the ratio of musicians to athletes is 3:1. This means that the number of musicians is 3 times the number of athletes. Hope this answers the question. Have a nice day.

Answer:  The answer is (D) The number of musicians is 3 times the number of athletes.

Step-by-step explanation:  Given that the ratio of musicians to athletes in a school is 3 : 1. We are to select the correct statement out of the given four options.

Since the total number of people are not given, so we cannot say that 13 of them are musicians. Therefore, option (A) is incorrect.

If there are 18 people, then number of athletes is given by

(x)/(x+3x)* 18=4.5\neq 12,

and hence the option (B) is not correct.

If there are 3 athletes, then

x=3, and so the number of musicians = 3 × 3 = 9 ≠ 12. Therefore, the option (C) is not correct.

Number of musicians = 3x = 3 × x = 3 × number of athletes.

Thus, the correct option is (D) The number of musicians is 3 times the number of athletes.

What is -4x=-2+4y -4y=1-4x

Answers

I hope this helps you

[6.02] For the following system, if you isolated x in the first equation to use the Substitution Method, what expression would you substitute into the second equation?-x - 2y = -4
3x + y = 12

Answers

To use the substitution method we need to convert one equation in terms of a certain variable and substitute this equation to the other equation. For this case we are asked to substitute the first equation to x in the second equation. Therefore, the equation to substitute is:

-x - 2y = -4
x = 4 - 2y

Answer:B

Step-by-step explanation:

2y-4

1)If (x-2) is a factor of x2+ 3ax -2a, then find the value of a

Answers

Answer:

x - 2 => x = 2

x² + 3ax - 2a

=> 2² + 3 × a × 2 - 2 × a

=> 4 + 6a - 2a

=> 4 + 4a

=> 4 ( 1 + a )

★ 1 + a = 0

a = -1

How do I simplify this polynomial

Answers

25x^5/5x^2

You need to divide 25 by 5 and subtract the exponent

5x³


I hope that's help:0